Challenges and Strategies in Achieving Financial Transparency at Tadika Al Fikh Orchard Pendamar Indah Selangor Malaysia - Alya Annisa Salwa Ritonga; Alfi Amalia (International Conference on Islamic Economic (ICIE), 2026)
This study aims to analyze the implementation of financial management transparency at Tadika Al-Fikh Orchard Pandamar Indah and to examine the role of Islamic values in financial practices within an early childhood Islamic educational institution. The research employs a qualitative approach with a descriptive-interpretative design to gain an in-depth understanding of the dynamics of financial governance in an Islamic institutional context. The research participants included the principal, treasurer, teachers, and representatives of parents. Data were collected through in-depth interviews, non-participant observation, and document analysis. Data analysis was conducted through the stages of data condensation, data display, and conclusion drawing and verification. The validity of the findings was ensured through source and method triangulation techniques. The findings indicate that efforts toward financial transparency have been undertaken through the periodic disclosure of fund utilization to parents. However, the implementation has not yet been standardized within a systematically documented reporting system. The main challenges include limited technical competence of financial administrators, reliance on manual bookkeeping systems, and minimal use of digital technology in financial administration. Furthermore, Islamic values such as amanah (trustworthiness), tabligh (transparency in conveying information), and fathanah (professional competence) are understood as moral foundations in financial management, yet they have not been fully integrated into operational procedures and accountable, measurable reporting mechanisms. This study highlights that strengthening financial transparency and accountability in Islamic educational institutions requires integrating human resource development, digital financial systems, and the internalization of Islamic values to achieve professional, sustainable, and integrity-driven governance practices.